Standardization of Telang Flower Extract for Bioactive Compound Assessment using Solvent Variations - Prasasti, Azmi; Prayudeni, Sari; Wijiani, Nina; Alfiansyah, M.Dzikry; Dwi Sasongko, Rio (Chemistry Education Department, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga, 2025)
Telang flowers are found in many tropical areas, one of whuch is in Indonesia. The content of telang flowers can be used as anticancer, anti-inflammatory and antimicrobial. The amount of healt potential contained in telang flowers is important to do standardization. This study aims to determine the standardisation of telang flower extract in maceration method with 96% etanhol, ethyl acetate and n-hexane solvents. Standardisation testing includes specific and non-specific parametes. The results showed that the telang flowers used was included in the Clitoria ternatea species. Weight yield, drying shrinkage, specific gravity, moisture content and ash content have met the standard. The largest yield weight is found in ethanol solvent which is 11.83%. The highest secondary metabolite content was found in ethanol solvent, namely alkaloids, flavonoids, tanins, and saponin. While in n-hexane solvent there were only terpenoids and steroids.